2015
DOI: 10.1007/s10856-015-5572-6
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure-modified biodegradable magnesium alloy for promoting cytocompatibility and wound healing in vitro

Abstract: The microstructure of biomedical magnesium alloys has great influence on anti-corrosion performance and biocompatibility. In practical application and for the purpose of microstructure modification, heat treatments were chosen to provide widely varying microstructures. The aim of the present work was to investigate the influence of the microstructural parameters of an Al-free Mg-Zn-Zr alloy (ZK60), and the corresponding heat-treatment-modified microstructures on the resultant corrosion resistance and biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…In this study, Mg-6Zn-0.5Zr alloy in the form of ZK60 (Zn 5.3 wt %, Zr 0.3 wt %, and balance Mg) was used as the metallic substrate, as it is a good candidate for medical applications with good biocompatibility [ 22 , 23 ]. The main alloying elements in ZK60 are zinc, participating the bone formation process, and zirconium, a trace element in our bodies.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Mg-6Zn-0.5Zr alloy in the form of ZK60 (Zn 5.3 wt %, Zr 0.3 wt %, and balance Mg) was used as the metallic substrate, as it is a good candidate for medical applications with good biocompatibility [ 22 , 23 ]. The main alloying elements in ZK60 are zinc, participating the bone formation process, and zirconium, a trace element in our bodies.…”
Section: Introductionmentioning
confidence: 99%
“…The new bone volume fraction with the ARRm-H380 membrane approached almost 100% after 12 weeks implantation. Previous reports have verified that Mg ions act as a stimulator to enhance cell proliferation and migration, and that the functional biochemical stimulation of Mg ions can improve wound healing in vitro and in vivo [7,30]. To the best of our knowledge, this report is the first to discover that Mg-based materials are capable of being applied in dentistry with excellent outcomes.…”
Section: In Vivo Degradation and Bone Healing Situationmentioning
confidence: 52%
“…Results revealed that ZK30-0.5Ag exhibited a reduced corrosion rate of 1.41±0.13 mm·year −1 , which was significantly smaller than that of ZK30 with a corrosion rate of 2.39±0.22 mm·year −1 . Compared with some other typical biodegradable Mg alloys, such as ZK60 [ 22 ] and Mg-1Ca [ 23 ], ZK30-0.5Ag exhibited an enhanced corrosion resistance with a small degradation rate, as listed in Table 1 . For extremely individual Mg alloys with particular structure, such as Mg 69 Zn 27 Ca 4 bulk metallic glass [ 24 ], it exhibited a smaller degradation rate than ZK30-0.5Ag, which could be ascribed to the fact that the amorphous structure promoted the formation of more passive oxide film on Mg matrix.…”
Section: Resultsmentioning
confidence: 99%